Indexing Executive Functions with Test Scores, Parent Ratings and ERPs: How Do the Measures Relate in Children versus Adolescents with ADHD? - Häger LA (Dove Medical Press, 2020)
Linda Angelica Häger,1,2 Geir Øgrim,1,2 Maria Danielsen,1 Eva Billstedt,2 Christopher Gillberg,2 Jakob Åsberg Johnels2,3 1Neuropsychiatric Team, Åsebråten Clinic, Østfold Hospital Trust, Fredrikstad, Norway; 2Gillberg Neuropsychiatry Centre, Institute of Neuroscience and Physiology, University of Gothenburg, Gothenburg, Sweden; 3Speech and Language Pathology Unit, Institute of Neuroscience and Physiology, University of Gothenburg, Gothenburg, SwedenCorrespondence: Linda Angelica HägerNeuropsychiatric Team, Åsebråten Clinic, Østfold Hospital Trust, 1740 Grålum, Fredrikstad PB300, NorwayTel +47 93 28 76 77Email Linda.Hager@so-hf.noObjective: Rating scales and neuropsychological tests including continuous performance tests (CPTs) are widely used to assess executive functions (EFs). Event-related potentials (ERPs) are also used to index certain EFs such as action preparation and inhibition. In this descriptive study, we examined the associations between results on an EF rating scale, a CPT and ERP components in ADHD as a function of age.Methods: Fifty-nine patients with ADHD (and more often than not with comorbid disorders) in two age groups (9– 12 years and 13– 17 years) were assessed using EF ratings, a visual CPT and ERPs (CueP3, P3go and P3no-go).Results: There were age related changes in the ERPs with the CueP3 amplitude being stronger in children, and the P3no-go amplitude stronger in adolescents. The associations between the EF measures were different in the two age groups. In particular, the P3no-go seemed to reflect different EF-related processes in children versus adolescents.Conclusion: Age group effects were seen on a selection of ERP amplitudes in this sample of patients with ADHD. Ratings, test scores and EF-related ERPs seem to capture different aspects of EF in ADHD, and the associations differed depending on age group. The results show that different measures of EF are not interchangeable and highlight the importance of age when interpreting ERPs.Keywords: executive functions, ADHD, electrophysiology, ratings, event related potentials, cognitive control